Characteristics of Cucumber Powder Drink (Cucumis sativus L.) With Addition of Lime Juice and Concentration of Maltodextrin Foam Mat Drying Method: Karakteristik Minuman Serbuk Mentimun (Cucumis sativus L.) Dengan Penambahan Sari Jeruk Nipis Dan Konsentrasi Maltodekstrin Metode Foam Mat Drying - Zakiyah, Mei Dita Fitrotus; Budiandari, Rahmah Utami (Procedia of Engineering and Life Science, 2023)
This study aims to determine the effect of adding lime juice and maltodextrin concentration on the characteristics of cucumber powder drink (Cucumis sativus L.) using the foam mat drying method. The method used in this study was a randomized block design (RBD) using two factorials consisting of lime juice with a concentration of (5%, 15%, 25%) and a concentration of maltodextrin (15%, 20%, 25%). So that there were 9 treatment combinations. Each treatment was repeated 3 times, so that 27 trials were obtained. Data analysis was carried out using ANOVA and follow-up tests with a 5% level of Honest Significant Difference and organoleptic tests were analyzed using the Friedman test. The results showed that there was no interaction between the concentration of lime and the concentration of maltodextrin on the levels of vitamin C in cucumber powder, but there was an interaction between the concentration of lime and the concentration of maltodextrin on the solubility of cucumber powder. The results showed that the lowest value for the water content parameter was 17.5%, the highest value for vitamin C was 1.287% and the highest value for the solubility parameter was 147.16%.